Cognitive reserve and lifestyle: moving towards preclinical Alzheimer’s disease - Arenaza-Urquijo, Eider M.; Wirth, Miranka; Chételat, Gaël (Frontiers in Aging Neuroscience, 2015)
The large majority of neuroimaging studies in Alzheimer’s disease (AD) patients have supported the idea that lifestyle factors may protect against the clinical manifestations of AD rather than influence AD neuropathological processes (the cognitive reserve hypothesis). This evidence argues in favor of the hypothesis that lifestyle factors act as moderators between AD pathology and cognition, i.e. through indirect compensatory mechanisms. In this review, we identify emerging evidence in cognitively normal older people that relate lifestyle factors to established AD neuroimaging biomarkers. While some of these investigations are in agreement with the compensatory view of cognitive reserve, other studies have revealed new clues on the neural mechanisms underlying beneficial effects of lifestyle factors on the brain. Specifically, they provide novel evidence suggesting direct effects of lifestyle factors on AD neuropathological processes. Here, we review current findings on the effects of lifestyle factors on AD neuroimaging biomarkers in cognitively normal older people. We propose a tentative theoretical model where lifestyle factors may act via direct neuroprotective and/or indirect compensatory pathways. Importantly, we suggest that neuroprotective mechanisms may have a major role during early stages and compensatory pathways in later stages of the disease. In the absence of an effective treatment for AD and considering the potential of lifestyle factors in AD prevention, understanding the neural mechanisms underlying lifestyle effects on the brain seems crucial. We hope to provide an integrative view that may help to better understand the complex effects of lifestyle factors on AD neuropathological processes, starting from the preclinical stage.